2018
DOI: 10.3329/jasbs.v44i2.46556
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Service Area of Cyclone Shelter and Vulnerable Households Using Network Analyst Tool: a Case Study on Southkhali Union of Bagerhat District, Bangladesh

Abstract: In Southkhali Union of Bagerhat district in Bangladesh about 47% of the total population is living beyond the service area of cyclone shelters (CS) not only for the carrying capacity of CS but also for the accessibility. Location-allocation tool of Network Analyst tool in ArcGIS determined the service area of each CS in the study area based on its shelter capacity and accessibility. People residing outside the service area of cyclone shelter are highly vulnerable due to low elevation of land and poor housing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Inadequate cyclone shelters in the locality and the need to travel long distances to the shelter were also responsible for non-compliance with the evacuation order, which took place at the rates of 21.92% and 23.74%, respectively. According to the Cyclone Shelter Construction, Maintenance and Management Policy-2011 of Bangladesh, cyclone shelters should be located within a 1.5 km distance from the housing areas to allow quick evacuation during a hazard (Hossain and Rahman 2018 ; Hossain et al 2014 ). A cyclone shelter buffer analysis based on a distance of 1.5 km found that most of the areas in Kalaroa (0%) and Tala Upazila (4.22%) were unserved by shelters.…”
Section: Resultsmentioning
confidence: 99%
“…Inadequate cyclone shelters in the locality and the need to travel long distances to the shelter were also responsible for non-compliance with the evacuation order, which took place at the rates of 21.92% and 23.74%, respectively. According to the Cyclone Shelter Construction, Maintenance and Management Policy-2011 of Bangladesh, cyclone shelters should be located within a 1.5 km distance from the housing areas to allow quick evacuation during a hazard (Hossain and Rahman 2018 ; Hossain et al 2014 ). A cyclone shelter buffer analysis based on a distance of 1.5 km found that most of the areas in Kalaroa (0%) and Tala Upazila (4.22%) were unserved by shelters.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the district of the coastal area of Bangladesh is physically vulnerable for riverine floods, tropical cyclones, devasting storm surges, erosion, which have severe economic and social disruption and considerable loss of life (Benson & Clay, 2003). For example-cyclone is a result of tropical monsoon climate, the nearest position from equator, worm oceanic temperature, presence high vertical wind, low-pressure areas in the Bay of Bengal and Chottogram, Cox's Bazar, Khulna, Noakhali are extremely vulnerable districts in Bangladesh having been located near the Bay of Bengal (Hossain et al, 2019;Hussain & Rahman, 2018 ). Sidr in 2007 is a real example of it for which about 3406 people have died, 55,282 people were injured and a total of $1.67 billion was damaged (Dasgupta et al, 2010).…”
Section: B) the Physical Vulnerabilitymentioning
confidence: 99%
“…First of all, Bangladesh is the 6 th most disaster-prone countries in the world in which 97.7 percent of the total population and 97.1 percent of total areas are at risk and threatened by climate change, including-sea level rising, storm surge, coastal cyclone, etc. (Hussain & Rahman, 2018;Goosen et al, 2018). It is clear that to maintain economic growth and alleviate poverty, Bangladesh has to reduce the vulnerability of cyclone instantly (Goosen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%